A Comprehensive Review on Antimicrobial Activity of Edible Biofilms - Jabbar, Muhammad; Shahid, Hamna; Hira, Hasooba; Kanwal, Hafsa (PSM Biological Research, 2023)
Latest trends are emerging for food packaging, which is beneficial for human health and overcoming environmental issues. Edible biofilms are protective coverings made up of polysaccharides, proteins, and lipid-based natural edible polymers and then applied outside the food product as an alternative solution to conventional packaging. Biodegradable edible biofilms extend the shelf life of foods, protect food from different food-borne pathogens, minimize the harmful impact of synthetic preservatives, provide better moisture and gas barrier properties, and improve nutritional values. Natural antimicrobial agents are used to enhance the antimicrobial activity of packaging. Here, we review the incorporation of natural polymers into the edible biofilm and how they affect specific food quality characteristics. About different types of edible biofilms and their applications on food while describing advantages and drawbacks. Limitations, use of nanoparticles in edible biofilms, and safety concerns.